QUANTITATIVE COMPOSITION OF CHEMICAL ELEMENTS AND VITAMINS IN PHLOMOIDES NUDA (Scientific journal of the Fergana State University, 2025)
The article presents the results of an experimental determination of the quantitative composition of 44 elements in the flowers, stems, and leaves of the Phlomoides nuda plant using the inductively coupled plasma mass spectrometry (ICP-MS) method. The NEXION-2000 equipment was used in the study. The main quantitative components in flowers include: potassium (K) – 9912.858 mg/kg, phosphorus (P) – 934.078 mg/kg, magnesium (Mg) – 1704.564 mg/kg, and calcium (Ca) – 1578.431 mg/kg. These elements are also the main components in leaves and stems; however, potassium and sodium concentrations are 4-5 times higher in the stem. The vitamin content in plant raw materials was determined using the HPLC method. The results showed that ascorbic acid (1.524 mg/g) is the main quantitative component, while among B-group vitamins, thiamine (1.877 mg/g) was found in the highest amount.